(untitled) (Research, Society and Development, 2023)
This article seeks to demonstrate how the use of audiovisual resources can contribute to the learning process in medical graduation. This is an experience report on the use of audiovisual resources in the learning process of medical graduation, linked to the Teaching-Service-Community Integration axis. The use of the audiovisual resource occurred through the television series entitled: Basic Unit. Two episodes were used that served as the basis for using the Methodology of theoretical-practical Problematization of the themes worked on during the experience of the axis: territorialization and teamwork in Primary Care. Audiovisual resources are important for teaching-learning, as they elucidate the content in a playful and understandable way, allowing students to associate the content studied in the classroom with the reality presented in the series, thus creating a critical reasoning to deal with situations that may arise in their future professional practice in Basic Health Units.